Cover Image. (14th September 2018) - Zhou, Mingdong; Lian, Haojie; Sigmund, Ole; Aage, Niels
Abstract : The cover image, by Mingdong Zhou et al., is based on the Research Article Shape morphing and topology optimization of fluid channels by explicit boundary tracking, https://doi.org/10.1002/fld.4667 .